The Consequences of School Violence: A Systematic Review and Meta-Analysis, Global, 1990-2016 - Polanin, Joshua R. ([Verlag nicht ermittelbar], 2021)
This project seeks to to provide clear and comprehensive answers to the questions that plague researchers on how school violence impacts future student outcomes. To that end, the principal investigators plan to review, organize, and synthesize extant research on consequences of school violence and aggression for perpetrators and victims by conducting a systematic review and meta-analysis on longitudinal studies of school violence and outcomes. The primary goal of the current study is to conduct a systematic review and meta-analysis of the extant longitudinal research literature on the consequences of school violence.